Pendekatan Object Oriented UX pada Perancangan Aplikasi Manajemen Order - Falahah; Prayudi Utomo (Ikatan Ahli Informatika Indonesia, 2020)
Building a better information system or application needs a good user experienced design, to ensure that the system is useful for users and easy to use. Usually, the process of UX design was not carried out systematically and only relies on intuition analysis or system designer. One of the systematic approaches in UX design is user-centered design, but the implementation still needs to be more detail because of the lack of systematics step and guide. One of these approaches is Object-oriented User Experience (OOUX) that can consider as a bridge between user-centered design and object-based application design. This study aims to explore OOUX, what is the steps, how to apply it to a case study on designing a system. The results show that OOUX can help the analysts on designing user experience more systematically, while producing the object candidates needed for object-oriented system design.